Temperament Models In A sample of basic education teachers Field Study In The City Of Lattakia (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research try to defined the Temperament Models of sample of Basic education teachers in Latakia city, as well as to identify differences in the differences between the mean responses of Basic education teachers on a scale of Temperament Models to the variables (sex, place of residence, Stage school). Use the search descriptive analytical method. Application a scale of Temperament Models on the sample included (274) male and female teacher, Pilot sample consisted of (50) teachers. Reliability was established by Cronbach – Alpha Reliability at lest (0.73) and (o.796) by Spearman-Brown. Results showed the field of the dynamic operations of Neurotic was the most spreading between teachers , and came after the field of the power to cease operations, at last the force in the excitement field , there are statistically significant differences according to six in favor of female, and there are statistically significant differences according to Stage school, there are no statistically significant differences according to place of residence.